Prevalence of camallanus cotti in poccilia reticulata obtained from some wastewater drains in Lagos state (2012)
One way to diversify Nigeria’s economy is to improve on agricultural activities with low import input but high export potential such as the promotion of the ornamental fish industry. P. reticulata is one such fish species that enjoys international acceptability. However, a potential bottleneck in its international trade is the decertification of exports from Nigeria in the uncertainty of standing parasite fauna of locally available stock of P. reticulata. Four Streets in different local government areas of Lagos State were identified with existing populations of P. reticulata where collection of samples with a scoop net was done before sorting into 60 male and 60 female individuals per wastewater drain from each Street was carried out monthly between March, 2004 and February, 2005. Temperature, pH, Dissolved Oxygen (DO), water transparency and drain depth were measured with mercury-bulb thermometer, ARH-1 CE electronic meter, Oxyguard electronic probe, secchi disc and calibrated pole respectively. Chi-square was used to test for sex-related differences in prevalence and ANOVA for differences in physicochemical analyses. Only 3.4% of the 4,320 samples examined were infected with C. cotti. There was no sex-related differences in the prevalence of C. cotti while only DO, transparency and drain depth were found to be significantly different among the wastewater drains on the four Streets. The highest prevalence of 15.0% was obtained in P. reticulata females obtained from Igi-Olugbin and Adenaike Alagbe Streets in September, 2004. High prevalence clustering correlated with receding rains. However, mean monthly temperature, transparency and drain depth were significantly different across drain (p < 0.05). P. reticulata obtained from these four Streets can be further exploited for import substitution and export market since this prevalence level can be managed and does not rival records of C. cotti in other popular export sources in Asia